Practitioners' perception on the adoption of user involvement in SDLC / Muhammad Ikhwan Faiz Ahmad Ainuddin - Ahmad Ainuddin, Muhammad Ikhwan Faiz (2011)
Recently, the existence of good software that meets the user requirements is very limited. Many of the software produced did not meet the expectations. In order to produce quality software that meets the user expectation, user involvement is important. This is where HCI practices is involved in software development. Usability engineering, user centered design, and participatory design are the terms that focusing on the user involvement in software development. This study has conducted a survey to 150 respondents who are the practitioners of software development in Klang Valley. The objective of this research is to obtain practitioners perception on the adoption of users involvement in SDLC and what is the factors to encourage or inhibit it. The result shows that communication between users and developers is importance in ensuring adoption of user involvement in software development becomes successful. However, most of the practitioners in software development agree that a difficulty occurs on adopting user involvement. The findings of this research will be helpful to decision making and further research regarding to the HCI practices in SDLC.